Pluralité des rapports aux normes professionnelles et politisation des pratiques dans la police turque des années 1970 - Benjamin Gourisse (European Journal of Turkish Studies, 2009)
This paper analyses the way Turkish policemen were politicized in the 1970s. It relies on the study of interns’ socialization into the police force. The article first examines some of the different paths by which individuals became police in order to understand why new recruits entered the force, and why some failed to integrate into institutional norms. Secondly, the article examines the working conditions of the police, suggesting that factors such as poor pay and insufficient resources (vehicles, uniforms, weapons, etc) made it more difficult for new recruits to develop a strong relationship with the institution. Finally, the article studies the impact of two mutually antagonistic associations that represented the police (Pol-Der and Pol-Bir). The paper argues that lack of training, discretional appointments, and limited resources explain why police during this time tended to become highly politicized and loyal to political organizations rather than primarily loyal to the police force itself.